ANALYSIS OF IMPACT FORCE AND MUSCLE ACTIVITY ON RESPON HEAD\'S CHILDREN IN SOCCER HEADING - Agung Supriyanto, Nugroho
Background and Objective: One of the important techniques in soccer is heading the ball which is used in the offense and defense plays. Heading doesn't use head protection, so it can lead to head injury. Children are at high risk of injury when heading the ball because their anatomy and physiology aren't well prepared yet and lack of understanding about doing heading technique correctly This study aimed to evaluate impact force and also sternocleidomastoideus muscle activity according to the ball size and heading's technique with and without body swing (backswing) on head response of children. Methods: Evaluation will be performed by using 30 subjects and head model of children and adults. Measuring instruments used accelerometer sensor to measure the impact force/collision based on changes in acceleration and electromyography to record sternocleidomastoideus muscle activity when heading the ball. Results: Backswing had a greater impact force rather than without backswing so this heading technique can be used in defense and offense plays and must be supported by greater muscle activity in order to avoid head injury. Backswing had the weakness which required right timing to get well prepared and also greater collision. Muscle activity resulting on children were smaller than adolescents and adults, so that the children were at high risk of head injury and neck fracture because they absorbed the impact force more than adolescent and adults. Impact force received by the children head model was larger than adolescent head model (p <0,01). The greater size of the ball will give more head impact force while the smaller the mass of the head, the greater the collision received. Conclusions: children are at high risk of injury because their head mass and circumference still small, and also weak in muscle activity. It is necessary using appropriate ball size and doing strength training correctly. Heading technique with body swing resulted in greater momentum and muscle activity so this technique can reduce the head injury.